2021
DOI: 10.1016/j.puhe.2020.11.021
|View full text |Cite
|
Sign up to set email alerts
|

Racial disparities in COVID-19 hospitalizations do not lead to disparities in outcomes

Abstract: Objectives Identification of racial differences in characteristics and comorbidities in patients hospitalized for COVID-19 and the impact on outcomes. Study design Retrospective observational study. Methods Data for all patients admitted to seven community hospitals in Michigan, United States with polymerase chain reaction confirmed diagnosis of COVID-19 from March 10 to April 15, 2020 was analyzed. The primary outcomes of racial disparity in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
21
1
4

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(27 citation statements)
references
References 25 publications
1
21
1
4
Order By: Relevance
“…This is consistent with findings from both national and international studies (8,38). The likely causes of racial-/ethnic-health disparities in COVID-19 outcomes were discussed extensively in prior studies (9,11,14,16,37,(39)(40)(41)(42)(43)(44). Some literature argued that minority communities may be more susceptible to severe complications of COVID-19 because of existing disparities in underlying conditions known to be associated with COVID-19 mortality, including hypertension, cardiovascular disease, kidney disease, and diabetes.…”
Section: Discussionsupporting
confidence: 82%
“…This is consistent with findings from both national and international studies (8,38). The likely causes of racial-/ethnic-health disparities in COVID-19 outcomes were discussed extensively in prior studies (9,11,14,16,37,(39)(40)(41)(42)(43)(44). Some literature argued that minority communities may be more susceptible to severe complications of COVID-19 because of existing disparities in underlying conditions known to be associated with COVID-19 mortality, including hypertension, cardiovascular disease, kidney disease, and diabetes.…”
Section: Discussionsupporting
confidence: 82%
“…Our study found that several social determinants of health put patients at risk for hospitalization during COVID-19 infection, including lower socioeconomic status, indexed by zip code and employment status, race, ethnicity, English as a second language, and public insurance. Prior studies have associated similar disparities – such as ethnic and racial minority groups, 7–11 poverty, 5 lower education levels, 4 public insurance coverage 5 , 6 , 11 – with higher hospitalization rates in those infected with COVID-19, yet the topic remains understudied, 7–11 and only few have focused on the risk of inpatient admission as a primary outcome 4 , 6 , 9–11 or addressed the breadths of social determinants, as our study has.…”
Section: Discussionmentioning
confidence: 90%
“…1 Clinical predisposing factors for hospitalization including: older age, male gender, obesity, COVID-19 Risk of Complications Score have been reported in southeast Michigan, a region significantly impacted by the pandemic. 2,3 Ethnic and racial minorities, poverty, and low education levels, 4 poverty and black race, [5][6][7][8][9] non-Hispanic black race, [7][8][9][10] public insurance use (ie, Medicare or Medicaid) 5,6,11 have been reported as health-care disparities having high hospitalization rates.…”
Section: Introductionmentioning
confidence: 99%
“…Our results suggest that the mechanism driving convergence is primarily affecting mortality within the county level, and is potentially linked to changes in cumulative COVID-19 prevalence rather than time. Given prior evidence that conditional on hospitalization, mortality among Black and White COVID-19 patients is similar, we discuss potential mechanisms upstream of hospitalization (Goyal et al, 2020; Krishnamoorthy et al, 2021; Moore, 2020; Renelus et al, 2020).…”
Section: Discussionmentioning
confidence: 99%